If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + x)(3x + 10) = 0 Reorder the terms: (9 + x)(10 + 3x) = 0 Multiply (9 + x) * (10 + 3x) (9(10 + 3x) + x(10 + 3x)) = 0 ((10 * 9 + 3x * 9) + x(10 + 3x)) = 0 ((90 + 27x) + x(10 + 3x)) = 0 (90 + 27x + (10 * x + 3x * x)) = 0 (90 + 27x + (10x + 3x2)) = 0 Combine like terms: 27x + 10x = 37x (90 + 37x + 3x2) = 0 Solving 90 + 37x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (9 + x)(10 + 3x) = 0Subproblem 1
Set the factor '(9 + x)' equal to zero and attempt to solve: Simplifying 9 + x = 0 Solving 9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + x = 0 + -9 x = 0 + -9 Combine like terms: 0 + -9 = -9 x = -9 Simplifying x = -9Subproblem 2
Set the factor '(10 + 3x)' equal to zero and attempt to solve: Simplifying 10 + 3x = 0 Solving 10 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = 0 + -10 3x = 0 + -10 Combine like terms: 0 + -10 = -10 3x = -10 Divide each side by '3'. x = -3.333333333 Simplifying x = -3.333333333Solution
x = {-9, -3.333333333}
| y+29=3y-33 | | -210/48 | | 1.5(x+8)=6.4+0.8 | | 9.6x=23.04 | | 0=X^2+X+3 | | 1024=x-252 | | P(x)=x-252 | | 1/6x | | (14*(1/6))-(10(11/24)) | | 1/5+x=7/12 | | 7x+6y=5 | | x-11=69 | | 3y=-0.09 | | 3x+c=5y | | .07x+.38=-.16-.05x | | 1-5(2x-4)=12 | | 3x+5+12x+7x=-14x-12+1 | | 0=x^2-5x+6 | | 12y-5=24y+4-13 | | -12w-4+3w-7=4 | | 3(5y-3)=6y | | 3x-4x-4=0 | | 4y+14=3 | | 6y-3(y-3)+6= | | 5p-22=-30+4p | | 3x-29=-23+9x | | 6.75+b=7.5 | | 66.8*2x=30 | | B=yx+m | | -x^2-3x-8=0 | | w/10=6 | | -1/6-7-7 |